Direction Given Under The Legal Aid, Advice and Assistance (Northern Ireland) Order 1981 : Interim Payments in Cases Funded under Article 10A: Interim Payments in Cases Funded under Article 10A. ([2017]) - Northern Ireland., Department of Justice,
No abstract available